Economic tour package model using heuristic - Abdul Rahman, Syariza; Benjamin, Aida Mauziah; Engku Abu Bakar, Engku Muhammad Nazri (2013)
A tour-package is a prearranged tour that includes products and services such as food, activities, accommodation, and transportation, which are sold at a single price.Since the competitiveness within tourism industry is very high, many of the tour agents try to provide attractive tour-packages in order to meet tourist satisfaction as much as possible.Some of the criteria that are considered by the tourist are the number of places to be visited and the cost of the tour-packages.Previous studies indicate that tourists tend to choose economical tour-packages and aiming to visit as many places as they can cover. Thus, this study proposed tour-package model using heuristic approach.The aim is to find economical tour-packages and at the same time to propose as many places as possible to be visited by tourist in a given geographical area particularly in Langkawi Island.The proposed model considers only one starting point where the tour starts and ends at an identified hotel.This study covers 31 most attractive places in Langkawi Island from various categories of tourist attractions. Besides, the allocation of period for lunch and dinner are included in the proposed itineraries where it covers 11 popular restaurants around Langkawi Island. In developing the itinerary, the proposed heuristic approach considers time window for each site (hotel/restaurant/place) so that it represents real world implementation. We present three itineraries with different time constraints (1-day, 2-day and 3-day tour-package).The aim of economic model is to minimize the tour-package cost as much as possible by considering entrance fee of each visited place.We compare the proposed model with our uneconomic model from our previous study. The uneconomic model has no limitation to the cost with the aim to maximize the number of places to be visited.Comparison between the uneconomic and economic itinerary has shown that the proposed model have successfully achieved the objective that minimize the tour cost and cover maximum number of places to be visited.